2018
DOI: 10.1029/2017jc013369
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dissipation in the Inner Surf Zone: New Insights From LiDAR‐Based Roller Geometry Measurements

Abstract: The spatial and temporal variation of energy dissipation rates in breaking waves controls the mean circulation of the surf zone. As this circulation plays an important role in the morphodynamics of beaches, it is vital to develop better understanding of the energy dissipation processes in breaking and broken waves. In this paper, we present the first direct field measurements of roller geometry extracted from a LiDAR data set of broken waves to obtain new insights into wave energy dissipation in the inner surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 102 publications
4
64
0
Order By: Relevance
“…The present study uses lidar and pressure data collected during the field experiments performed at Saltburn by the Sea, UK (Figure a), during April 2016 (Martins, Blenkinsopp, Power, et al, ; Martins et al, ). Similar to Martins, Blenkinsopp, Power, et al () and Martins et al (), we only use data from 9–10 April 2016, corresponding to a swell event characterized by a peak wave period Tnormalp=911 s and a significant wave height Hnormals=1 m. During these two days, a mean peak wave direction of 16.9°NE was measured at the nearshore buoy deployed in 17‐m depth, with a directional spread of 15.3°. Since the coastline around the pier is oriented toward 18°NE, incident waves were essentially propagating shore normal and parallel to the pier.…”
Section: Methodsmentioning
confidence: 99%
“…The present study uses lidar and pressure data collected during the field experiments performed at Saltburn by the Sea, UK (Figure a), during April 2016 (Martins, Blenkinsopp, Power, et al, ; Martins et al, ). Similar to Martins, Blenkinsopp, Power, et al () and Martins et al (), we only use data from 9–10 April 2016, corresponding to a swell event characterized by a peak wave period Tnormalp=911 s and a significant wave height Hnormals=1 m. During these two days, a mean peak wave direction of 16.9°NE was measured at the nearshore buoy deployed in 17‐m depth, with a directional spread of 15.3°. Since the coastline around the pier is oriented toward 18°NE, incident waves were essentially propagating shore normal and parallel to the pier.…”
Section: Methodsmentioning
confidence: 99%
“…. Although video is limited to daytime monitoring, the development of lidar technology is expanding the possibilities of shore-based remote sensing(Blenkinsopp et al 2010; Almeida et al 2015) and now offers an attractive alternative to monitor high frequency topography and runup or more recently, the detailed geometric properties of waves in the surfzone(Martins et al 2018). First long-term deployments are being conducted (e.g.…”
mentioning
confidence: 99%
“…Past work has shown that pressure-and lidar-based measurements of wave skewness and asymmetry are qualitatively consistent with one another, suggesting that lidar measurements can be used to analyze wave profile evolution across the surf-zone [28]. The linescan dataset described in this paper provides wave profile information at a high spatial and temporal resolution across the inner surf-zone, which could be used to further investigate the evolution of shoaling and breaking wave shapes near the shoreline [29][30]. Figure 10 shows an example of the evolving profile of two waves (separated by 20 min in time) as they propagate through the surf-zone.…”
Section: Short (Wave-by-wave) Time Scalesmentioning
confidence: 58%
“…In coastal areas, lidar scanners have been used to produce both large-scale coastal maps [18,19] as well as small-scale high resolution scans of nearshore morphology [20][21][22]. Additionally, lidar scanners are capable of providing returns off both the ground and the water surface, allowing for the assessment of beach and dune morphology (e.g., [20][21][22][23][24][25]) as well as wave transformation and water surface elevation in the swash and inner surf-zones [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%